1994
DOI: 10.1007/bf00121148
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemistry and cytotoxicity of ceramics

Abstract: General cytotoxicity was assayed for ceramic (AI20 a, ZrO2/Y2Oa, AIN, B4C, BN, SiC, Si3N 4, TiB, TiC, TiN) diamond and graphite powders, using 3T3 Balb/c permanent cell lines. Neutral red test was carried out in order to establish cell viability. Further investigations were undertaken on human differentiated cells (human umbilical venous endothelial cells): cell behaviour (MTT assay, total cell protein content) and differentiation (immunofluorescence) were studied. In both cases, no cytotoxic effect has been n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 15 publications
1
54
0
4
Order By: Relevance
“…Zirconium oxide is a radiopacifier with the characteristics of biocompatibility 25) and radiopacity 26) and an ability to accelerate hydration 27) . In a previous study of radiopacifier replacement in Portland cement, zirconium oxide was reported not to participate in the hydration reaction 28) and not to affect its physical properties 29) .…”
Section: Discussionmentioning
confidence: 99%
“…Zirconium oxide is a radiopacifier with the characteristics of biocompatibility 25) and radiopacity 26) and an ability to accelerate hydration 27) . In a previous study of radiopacifier replacement in Portland cement, zirconium oxide was reported not to participate in the hydration reaction 28) and not to affect its physical properties 29) .…”
Section: Discussionmentioning
confidence: 99%
“…20), 21) In vitro experimentation both by Covacci et al and Silva et al had showed absence of mutations 22), 23) and it is also not cytotoxic. 24)26) The mechanical properties of Zirconia are similar to Stainless Steel. Its resistance to tensile and compression resistance are about 9001200 MPa and 2000 MPa respectively.…”
Section: Zirconia Ceramicmentioning
confidence: 99%
“…Dental zirconia is a dense ceramic biomaterial that has a compression resistance of about 2,000 MPa [3]. Moreover, many investigations on the biocompatibility of yttria-modified zirconia have reported no cytotoxic effects on in vitro cell cultures [4] and no adverse in vivo tissue reactions in animals [5]. However, the bonding between zirconia and resin cement is relatively weak owing to the extremely inert character of zirconia.…”
Section: Introductionmentioning
confidence: 99%